Spatio-temporal dynamics of urban medical system carrying capacity and their obstacle factors: A case study of Yangtze River Delta urban agglomeration - Chengshuang Sun; Ke Zhou; Guangxia Li; Weina Zhu; Dongjun Wan (PLoS ONE, 2025)
The frequent occurrence of various urban disasters poses risks to human survival and welfare, and it is of great significance to evaluate the urban medical system carrying capacity (UMSCC), monitor the spatial and temporal patterns of the UMSCC and identify their obstacle factors to improve the public medical system and rationalize medical resource allocation. In this paper, the Yangtze River Delta urban agglomeration (YRDUA), which includes 27 major cities, is taken as a case study. A UMSCC evaluation model is constructed and the gravity center shift trajectory is analyzed by using the ArcGIS software. The results indicate that the UMSCC of the 27 cities in the YRDUA can be classified into 5 levels: the lowers (0.193-0.335), the lows (0.335-0.425), the mediums (0.425-0.489), the highs (0.489-0.549) and the highers (0.549-0.619). From 2011-2021, the UMSCC level in all the 27 cities from the YRDUA increased annually, and during this period, the gravity center of the UMSCC was concentrated in Xuancheng, and the migration trend was southwest. Moreover, there is a positive correlation between the city type and the level of UMSCC: the larger of the city is, the higher of the UMSCC level is; however, the gap between the levels of UMSCC in different city types in the YRDUA gradually narrows and tends to be consistent, which reflects the development trend of medical system integration in the region. Finally, it is concluded that the key obstacle indicators of the UMSCC in the YRDUA can be attributed to the proportion of medical financial expenditure, the number of beds, the number of registered nurses and the urban digital development level. Correspondingly, the suggestions are proposed.